PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL PENGAJARAN LANGSUNG DI SD - Sofnita, Lira (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the phenomenon in schools, where teachers explain many of the concepts to the facts when the IPS learning begins from facts to concepts, so that students' low. This study aims to describe how the design, implementation, and assessment of learning IPS with direct instructional model. Methodology in this research is qualitative research and quantitative research with observations and final test. This study has shown that learning IPS using learning model can directly improve student learning outcomes. Kata kunci : hasil belajar, pengajaran langsung, pembelajaran IPS.